2020
DOI: 10.3389/fcell.2020.568116
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of tRNA-Derived Small RNAs Discloses New Therapeutic Targets of Caloric Restriction in Myocardial Ischemic Rats

Abstract: Caloric restriction (CR) is a novel dietary therapy that has a protective effect on myocardial ischemia. However, the mechanisms underlying the therapeutic effect of CR remain unclear. Transfer RNA-derived small RNAs (tsRNAs) are a novel type of short non-coding RNAs that have potential regulatory functions in various physiological and pathological processes. In this study, we explored new therapeutic targets of CR through tsRNA sequencing. Rats were randomly divided into three groups: a normal control group (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Both tRFs & tiRNAs have also been identified as a novel biomarker for the treatment of skin melanoma ( Zheng et al, 2016 ). Other studies have shown that tsRNAs are potential therapeutic targets for caloric restriction pretreatment to improve myocardial ischemic injury ( Liu et al, 2020 ). Moreover, tsRNA is a potential therapeutic target for Buyang-Huanwu-Decoction (BYHWD) in the treatment of intracerebral hemorrhage (ICH), which provides new insights into the mechanism by which BYHWD promotes neural function recovery after ICH ( Li et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both tRFs & tiRNAs have also been identified as a novel biomarker for the treatment of skin melanoma ( Zheng et al, 2016 ). Other studies have shown that tsRNAs are potential therapeutic targets for caloric restriction pretreatment to improve myocardial ischemic injury ( Liu et al, 2020 ). Moreover, tsRNA is a potential therapeutic target for Buyang-Huanwu-Decoction (BYHWD) in the treatment of intracerebral hemorrhage (ICH), which provides new insights into the mechanism by which BYHWD promotes neural function recovery after ICH ( Li et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies have shown that tRFs and tiRNAs are highly conserved small ncRNAs fragments playing important roles in physiological and pathological conditions, such as development, 29 ageing, 30 neurodegenerative diseases, 31 cancer 32 , 33 , 34 and cardiovascular diseases. 35 Hence, they serve as rational therapeutic targets. 36 In the current study, it was hypothesized that differential expression of tRFs and tiRNAs play an essential role in the development of AS.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of the disease is divided into mild, moderate and severe, according to guidance for COVID-19 pneumonia diagnosis and treatment plan in China. Fold-change > 1.5 and P-value < 0.05 was used as the selection criteria [ 25 , 26 ]. Finally, we analyzed the potential clinical application value of autophagy-related genes identified in this study for evaluating the different disease severities of COVID-19 patients.…”
Section: Methodsmentioning
confidence: 99%